1999
DOI: 10.1542/peds.103.2.e24
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Continuous Positive Airway Pressure and Early Surfactant Therapy for Respiratory Distress Syndrome in Newborns of Less Than 30 Weeks' Gestation

Abstract: ABSTRACT. Objective. To determine whether early versus late treatment with porcine surfactant (Curosurf) reduces the requirement of mechanical ventilation in very preterm infants primarily supported by nasal continuous positive airway pressure (nasal CPAP).Design. Multicenter randomized, controlled trial.Patients. The study population comprised 60 infants <30 weeks' gestation with respiratory distress syndrome (RDS) who had an arterial to alveolar oxygen tension ratio (a/APO 2 ) of 0.35 to 0.22.The cohort from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
266
2
7

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 393 publications
(286 citation statements)
references
References 32 publications
11
266
2
7
Order By: Relevance
“…22 This last has been considered to be a ventilation mode with advantages over conventional mechanical ventilation in certain clinical situations, proving efficient at CO 2 elimination and capable of reducing the duration of ventilatory support and oxygen therapy because it makes use of different gas transport mechanisms than does conventional mechanical ventilation. 21,22 Lee et al, studying newborn babies, observed vibrations similar to those found in our study. They state that the vibrations produced by the water seal CPAP s bubbling are transmitted to the chests of the babies on this type of ventilatory support and could contribute to gas exchange.…”
Section: Test Lungsupporting
confidence: 91%
See 2 more Smart Citations
“…22 This last has been considered to be a ventilation mode with advantages over conventional mechanical ventilation in certain clinical situations, proving efficient at CO 2 elimination and capable of reducing the duration of ventilatory support and oxygen therapy because it makes use of different gas transport mechanisms than does conventional mechanical ventilation. 21,22 Lee et al, studying newborn babies, observed vibrations similar to those found in our study. They state that the vibrations produced by the water seal CPAP s bubbling are transmitted to the chests of the babies on this type of ventilatory support and could contribute to gas exchange.…”
Section: Test Lungsupporting
confidence: 91%
“…8 The mechanism by which gas exchanges occur during high-frequency ventilation have not been completed explained, but they probably include direct ventilation of the proximal alveoli and increased diffusion because of the increased activity of the gas molecules or even by means of coaxial diffusion in which the air enters via the center and the CO 2 and other gasses are exhaled via the peripheries of the airways. 1,21,22 …”
Section: Test Lungmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Early surfactant administration followed by extubation to nasal continuous positive airway pressure (NCPAP) or NCPAP alone without surfactant therapy have been shown to decrease the incidence of BPD in very low birth weight infants in observational studies. 5,6 Findings of a multicenter randomized controlled trial 7 investigating whether early versus late treatment with surfactant reduced the requirement of mechanical ventilation in very preterm infants primarily supported by NCPAP found that early surfactant treatment improved oxygenation 6 h after randomization and reduced the need for mechanical ventilation via endotracheal tube (MVET) before discharge from 68 to 25%. In addition, early surfactant administration followed by extubation to NCPAP in infants <30 weeks gestational age significantly decreased the need for MVET to 0% by 7 days of age compared with 43% in the mechanical ventilation group.…”
Section: Introductionmentioning
confidence: 99%
“…Since 1999, there have been six trials [29][30][31][32][33][34] evaluating the outcome of early surfactant therapy followed by extubation to NCPAP (Table 3). Overall, these reports demonstrated decreased duration of mechanical ventilation and length of stay, and decreased need for additional doses of surfactant.…”
Section: Surfactant Therapy and Nasal Continuous Positive Airway Presmentioning
confidence: 99%